Development of loop-mediated isothermal amplification for detection of Mycoplasma ovipneumoniae in goats, Capra hircus - Borang, Miti; Ramachandran Latha, Rathish; Mampilli, Pradeep; Melepat, Deepa Padinjare; Kaithathara, Vijayakumar (Journal of microbiological methods, 2024)
Mycoplasma ovipneumoniae is an important pathogen that causes respiratory disease in goats and sheep, leading to significant economic losses in the livestock industry. A quick and robust diagnostic test will aid in early diagnosis and treatment of the disease. Loop-mediated isothermal amplification (LAMP) offers several advantages over traditional PCR, including faster amplification, simpler operation, and lower equipment requirements, making it a promising tool for use in basic livestock units where resources and infrastructure may be limited. The present study reports on developing a LAMP assay to rapidly detect M. ovipneumoniae in goats (Capra hircus) targeting the 16S rRNA gene. LAMP was optimized to perform at 60 °C for 75 min. The result was visualized by a change in colour from deep pink to orange and further confirmed by gel electrophoresis, which gave a typical ladder-like pattern. The detection limit of the assay was as low as 0.04 ng/μl, indicating the high sensitivity of the assay. The test failed to amplify DNA isolated from healthy goat blood, Mycoplasma arginini DNA, and Staphylococcus aureus DNA. The sensitivity, specificity, and accuracy of the assay were 97.73% and 94.83%, and 96.08%, respectively. The study concludes that the developed loop-mediated isothermal amplification assay is a practical and reliable tool for field-level diagnosis of M. ovipneumoniae infections in goats, with high sensitivity and specificity under resource-limited conditions. •Respiratory mycoplasmosis due to Mycoplasma ovipneumoniae is common in goats (Capra hircus).•LAMP assay was standardized for point-of-care diagnosis.•The results of the assay was comparable to PCR-based diagnosis.•Clinical cases could be diagnosed with high-sensitivity.